'There is No Mother to Take Care of You'. Views of Unaccompanied Children on Healthcare, Their Mental Health and Rearing Environment. Issue 2 (3rd April 2019) - Zijlstra, A. E.; Menninga, M. C.; Van Os, E. C. C.; Rip, J. A.; Knorth, E. J.; Kalverboer, M. E.
ABSTRACT: This study aimed to shed light on the opinions of unaccompanied refugee children ( N = 98) in various care facilities in the Netherlands (small living groups, small living units, foster families, large reception centres) about their mental health, their healthcare needs and their rearing environment. A mixed methods design was applied. The quality of the child-rearing environment and the age on arrival in the host country proved to be predictive of mental health outcomes. Unaccompanied children living in large reception centres experienced the lowest quality of rearing environment, the highest mental health problems and poor access to mental healthcare. Implications for practice and research are reflected upon.